Policing migration and racial technologies - Parmar, Alpa (The British journal of criminology, 2019)
The merger between familiar modes of policing with the impetus for migration control is reorganizing the racial politics of policing in unexpected ways. In the aim to decipher who is a citizen, who is a foreign national offender and who is eligible for deportation on the grounds of criminality, the role of criminal records agencies has expanded further into the work of policing, as have the collaborative working partnerships between immigration and the police. In this article, I discuss the findings from research, which examines the policing of migration in the United Kingdom, and specifically Operation Nexus, which brings together ordinary police work and migration control. I focus on how technologies of border control are imbricated with everyday police practices that are often influenced by race, thereby deepening the reach of racial technologies and their capacity to monitor and exclude racial others.